2014
DOI: 10.1111/joor.12179
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory efficiency in complete denture wearers with reduced dental arches – a randomised cross‐over study

Abstract: One obstacle to placing artificial posterior teeth in manufacturing complete dentures is a reduction of the space between the maxilla and the mandible. Occasionally, second molar placement is not performed, as it does not affect aesthetics, phonetics or comfort. The aim of this study was to compare the masticatory efficiency between patients wearing maxillary and mandibular complete dentures with reduced dental arches (without second molars) (WSM) and with full dental arches (FDA). Twenty subjects were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The increase of bone volume seems to minimize the position effect of the teeth on the strain values recorded in the bone tissue. The small differences that do exist in strain between each of the implant sites may be because of the position that leads to a specific physiological load [41][42][43]. This may suggest that, in the absence of bone augmentation, further consideration needs to be given to the placement of the implant in atrophic ridges.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of bone volume seems to minimize the position effect of the teeth on the strain values recorded in the bone tissue. The small differences that do exist in strain between each of the implant sites may be because of the position that leads to a specific physiological load [41][42][43]. This may suggest that, in the absence of bone augmentation, further consideration needs to be given to the placement of the implant in atrophic ridges.…”
Section: Discussionmentioning
confidence: 99%
“…The natural food contains water, which might affect the results after the processing and drying of the test foods [18]. However, real food might psychologically influence mastication, thus the particle distribution could have been different [19]. The number of chewing strokes was set at 35 cycles for standardization.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the number of chewing cycles needed to swallow varies among people. If tests were performed with chewing until swallowing, the material distribution could also have been different [19].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of masticatory function is one of the possible examinations to estimate the quality and ability of food intake . Several food bolus sampling methods for the evaluation of masticatory function have been reported: (a) mixing ability test by using chewing gum or wax cubes during mastication, (b) particle analysis methods that retrieve all of a masticated test food (eg, peanuts and nuts), (c) particle analysis methods that retrieve all of a nonedible test material (eg, Optocal and Optosil) and (d) evaluation of content elution (eg, glucose or β‐carotene) using gummy jelly that retrieves all of a test food.…”
Section: Introductionmentioning
confidence: 99%
“…However, the differences in the actual particle properties between these conditions have not been reported so far. This saliva content argument would also cover the nonedible artificial test material used for the evaluation of masticatory performance, for example Optocal, because it also requires suppression of swallowing during mastication. In addition, the process model of feeding describes mastication and swallowing such that triturated food is propelled through the fauces for bolus formation in the oropharynx during chewing.…”
Section: Introductionmentioning
confidence: 99%